An integrative approach for species delimitation in the spider genus Grammostola (Theraphosidae, Mygalomorphae). (25th December 2015) - Montes de Oca, Laura; D'Elía, Guillermo; Pérez‐Miles, Fernando
Abstract : The mygalomorph genus Grammostola (family Theraphosidae) is endemic to South America. The species Grammostola anthracina is one of the largest spiders in Uruguay and reputed to be the longest lived tarantula in the world. This nominal species has two distinct colour morphs comprising black and reddish‐brown forms with controversial taxonomic status. Here, we present a phylogenetic study based on molecular characters (cytochrome c oxidase subunit I) of haplotypes of G. anthracina and closely related species. Our analysis together with new morphological data and biogeographical information indicates that the two morphs of G. anthracina constitute different species that are not sister to each other. Consequently, a new species, Grammostola quirogai is described, diagnosed and illustrated to encompass the black morph. Phylogenetic relationships and new taxonomic characters for Grammostola species included in this study are discussed.